Global Financial Crunch and India's Economic Growth: A Deep Insight - Singh, F. B.; Yadav, Ajay Pratap (Indian Journal of Finance, 2010)
The whole world was again reminded of the Great Depression of 1929 when on 15th September 2008; the world famous investment bank, Lehman Brothers filled their claim of bankruptcy.15th September 2008 was the day when the extent of the catastrophe of the financial market was made known to the entire world. It was just like a "financial tsunami". Infact, whether it was the Great Economic Depression of 1929 or the Financial Crisis of 2008, all these are genesis of the heedless race of interminable gain (capital).